2019
DOI: 10.1111/obr.12973
|View full text |Cite
|
Sign up to set email alerts
|

Physiological mechanisms underlying children's circannual growth patterns and their contributions to the obesity epidemic in elementary school age children

Abstract: Several studies since the 1990s have demonstrated that children increase their body mass index at a faster rate during summer months compared with the school year, leading some to conclude that the out-of-school summer environment is responsible.Other studies, however, have suggested that seasonality may play a role in children's height and weight changes across the year. This article reviews evidence for seasonal differences in the rate of children's height and weight gain and proposes potential physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 95 publications
(149 reference statements)
1
16
1
1
Order By: Relevance
“…The CCR Model of accelerated summer weight gain proposed that the lack of social demands during summer would result in more variable sleep timing, which may increase the risk of circadian misalignment during summer contributing to accelerated summer weight gain [26,27]. However, the current study found no evidence of school-summer differences in the variability of sleep timing and there was no association of variability in sleep timing with children's change in BMI during the school year or summer.…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations
“…The CCR Model of accelerated summer weight gain proposed that the lack of social demands during summer would result in more variable sleep timing, which may increase the risk of circadian misalignment during summer contributing to accelerated summer weight gain [26,27]. However, the current study found no evidence of school-summer differences in the variability of sleep timing and there was no association of variability in sleep timing with children's change in BMI during the school year or summer.…”
Section: Discussioncontrasting
confidence: 78%
“…The effect of age was allowed to vary across participants and controlled for differences in the number of days between BMI assessments across participants. Variables were selected a priori for inclusion in the model based on theory [26,27] and previous research demonstrating differences in children's sleep across sex [55], race [56], age [57], and chronotype [58].…”
Section: Statistical Design and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Similar patterns have been observed among school-aged children ( 1 ) and in 2 previous studies of preschoolers ( 2 , 4 ), adding to the evidence that efforts to promote healthy child weight may be most needed in summer. The lack of a structured daily schedule ( 10 ), the biological response to longer day length ( 11 ), or both may explain accelerated summer weight gain. However, more research is necessary among preschool-aged children, because another study found a decrease in BMIz over the summer among preschool-aged children with obesity ( 3 ).…”
Section: Discussionmentioning
confidence: 99%